Comparison of energy and macro-nutrients intakes in university hostel students in two countries of Asia - Khattak, Muhammad Muzaffar Ali Khan; Abu Bakar, Ibrahim; Draman, Samsul; Khan, Alam; Khattak, Muzaffar (2008)
Objective: The aim of this was to compare energy and macro-nutrients intakes in university hostel students in two Ccuntries of Asia Methods: Female students from the hostels of International Islamic University, Malaysia, Kuantan Campus and NWFP, Agricultural University Peshawar- Pakistan were assessed for the energy and macro-nutrients intakes. A total of 140 students were registered who volunteered to participate in this study. The age range of the registered students was 22-26 years. On the day of the registration, age, height and weight were recorded; also, food frequency questionnaires (FFQs) were provided. The participants were asked to record alternately for three days whatever they ate during the prescribed week. Out of 140 students 139 returned the FFQs and one of the students failed to return therefore excluded from the study. From the anthropometry, the BMI was used to assess the under, ideal, over-weight and obese students. From the FFQs, energy and nutrient intakes were calculated using the food composition Tables for Malaysia & Pakistan and compared with the recommended nutrients intakes (RNIs). Results: The body weight for the required height among the Malaysian students was lower by 7.81 percent than the reference value whereas the body weight of Pakistani students matched to the reference weight for height (Table 1). The Malaysian students were 28.0, 61.0, 5.5 and 0.9 % under, ideal, over-weight and obese respectively whereas Pakistani students were 100 % in the category of ideal-body weight. The total energy consumption was higher among Malaysian students by 9.93 % compared to the reference requirements whereas the Pakistani students claimed to meet the requirements. In terms of nutrients balancing the Malaysian students were having the ideal combination of the macro-nutrients and it was within the recommended range of 55-60, 15-20 and 25-30 % for carbohydrates, protein and fat respectively. These were poor among the Pakistani students and meet the energy requirements at the expense of fat consumption. Conclusions: This study suggests that there is imbalance in macro-nutrients intake among the students